A Comparative Study of Muslim and Non-Muslim Perceptions of Halal Food: Examining Trust and Confidence in Malaysia. - Chong, Ye Hao; Abdullah, Nor Hazana (Research in Management of Technology and Business, 2026)
Halal food is widely consumed in Malaysia by both Muslim and non-Muslim consumers; however, recurring concerns regarding consumer trust and confidence in halal certification have raised questions about how halal-labelled products were perceived across different religious groups. This study aimed to compare the perceptions of halal food between Muslim and non-Muslim consumers in Selangor and Johor Malaysia, focusing on factors that influenced their trust and confidence in halal-labelled products. A quantitative survey method was conducted with 324 respondents using quota sampling and data were analysed using SPSS. The Mann-Whitney U test was employed to identify the comparative differences, revealing a statistically significant difference (p